The optimal stability-oriented monetary policy: Optimal monetary policy under low trend inflation - Guido Ascari; Tiziano Ropele (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
In this paper we generalise the standard optimal monetary policy literature as in Galí (2003) to the case of positive trend inflation. We present a simple framework that provides straightforward analytical results directly comparable with the standard case. Optimal monetary policy is strongly influenced by trend inflation and becomes less effective in controlling inflation as trend inflation increases. Moreover: (i) under discretion, optimal monetary policy may not be implementable (i.e., indeterminacy arises) and the efficient policy frontier worsens; (ii) under commitment, the degree of interest rate smoothing increases with trend inflation and the gains from commitment are highly sensitive to the level of underlying inflation. An ECB-like stability oriented monetary policy (i.e., 2% target inflation rate in the medium term) determines a substantial percentage loss in welfare with respect to a zero inflation target policy.
Keywords: E24; E32; 330; optimal monetary policy; trend inflation; Geldpolitik; Inflation; Neukeynesianische Makroökonomik; Allgemeines Gleichgewicht; Regelbindung; Theorie